Population, Migration, Ageing and Health: A Survey - Christian Dustmann; Giovanni Facchini; Cora Signorotto (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We review the literature on recent demographic changes in Europe, focusing on two of the main challenges brought about by an ageing population: severe labor shortages in many sectors of the economy and growing pressures on both health and welfare systems. We discuss how and to what extent migration can contribute to address these challenges both from a short and a long term perspective. Finally, we identify several areas in which more research is needed to help devising more effective policies to cope with a greying society.
Keywords: 330